EXPLANATION OF THE TERMS OF HORTICULTURE IN UZBEK AND ENGLISH DICTIONARIES AND THEIR ISSUES - Diyarov Akmal To‘lqin o‘g‘li (Bright Mind Publishing, 2025)
This article discusses the creation of a bilingual dictionary for horticultural terms, emphasizing the importance of including not only the translation but also the scientific definitions, usage scope, and equivalent variants in multiple languages. The role of corpus linguistics in improving the quality of dictionaries and translation products is highlighted, along with the creation of language corpora that aid lexicographers in providing efficient translation equivalents. It also discusses the microstructure of the dictionary, including the elements of pronunciation, category, grammatical features, and examples, as well as the systematization of horticultural terms according to international lexicographic standards. The text also addresses the challenges of non-equivalence between English and Uzbek terms and proposes the development of a unified horticultural terminology base, which will enhance international collaboration in the field.
Keywords: Horticulture terminology, bilingual dictionary, corpus linguistics, lexicography, translation equivalents, microstructure, grammatical features, valency characteristics, lexicographic standards.